2020
DOI: 10.15294/edaj.v8i4.36311
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Institutions and Business Opportunities Toward Economic Growth

Abstract: This study aimed at explaining the relationship, and effects of human capital, entrepreneurial business opportunities, institutional economics, and regional economic growth. It was carried out to develop fundamental microeconomic model in rural development to assist human capital roles and institutions as well as entrepreneurial business for the economic growth. Further, the researchers used simultaneous system method in form of a recursive correlational path analysis model. This modeling system provides simpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Therefore, sample respondents need to be free from various political level interventions. Quantitative variable data is obtained using the Gini index value (IGX) measurement scale with the following formulation , 2020bPrasetyo, Setyadharma, & Kistanti, 2019).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, sample respondents need to be free from various political level interventions. Quantitative variable data is obtained using the Gini index value (IGX) measurement scale with the following formulation , 2020bPrasetyo, Setyadharma, & Kistanti, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, formal and informal institutional factors are contextual components included in social progress and promote entrepreneurial opportunities to achieve higher economic growth levels (Aparicio, Turroo, & Noguera, 2020). This means that the economic institution's contribution to development has far exceeded the availability of natural resources, the supply of other production factors, and technological advances (Acemoglu & Robinson, 2008;Prasetyo & Dzaki, 2020;Prasetyo, Setyadharma, & Kistanti, 2019). A recent literature study showed that the configuration of institutional conditions and social capital has led to a high prevalence rate of various social entrepreneurship activities in a country (Deng et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…By creating and enforcing economic rules and regulations, these institutions play a significant part in shaping the economy (Salman et al, 2019). Solid institutions that provide a stable and predictable economic environment can aid private sector development (Phucet al, 2019;Prasetyo et al, 2020). In addition to helping the government run smoothly, they ensure that the rule of law is upheld and that power is not abused in a political context.…”
Section: Introductionmentioning
confidence: 99%